Distribution Pattern of Trachoma in Pakistan and Monitoring the Effects of Water Availability upon Disease prevalence- case study of Khyber Pakhtunkhwa - Junaid Faisal Wazir, Saleem Rana, Noorulain Javaid, Shumaila Nargus, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Trachoma is the most crucial infectious disease and one of the biggest vectors leading to worldwide preventable blindness. After cataracts and glaucoma, being the most prevalent diseases, trachoma acquired a third place among the most common ocular diseases. It is among the seven most neglected tropical diseases and is accounted for 0.006 to 0.008 billion people (mostly women) suffering from optical deterioration predominantly living in poor resource habitats. Aim: To estimate the permeation of active trachoma and measure its burden in four districts of Khyber Pakhtunkhwa (KP). Additionally, it is aimed to determine the distribution patterns of the infection while considering factors such as, age, gender, and dwellings. Methodology: The sample size (n=3036) estimation is undertaken while considering the past minimal prevalence of trachoma in the country. The data based on structured questionnaire and observations’ study collected from four districts of KPK. Detailed analyses were conducted using SPSS 24.0 by using descriptive analysis, correlation and Chi Square test of independence. Results and conclusion: The first thing accomplished was the testing normality of data using the Shiparo Wilk test, and it is found that all the variables were abnormal. It is found that in most of the cases, the use piped water strongly influences the contamination and lead to increment in disease. The correlation result shows significant results stating the effect of decrease of animals in house improved trachoma grading. Keywords: Trachoma, Blindness, KPK, Semi-Structural Interviews